John L. Austin: the role of rethoric in the periphery of philosophy - Rodríguez Ponce, María Isabel (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
This paper analyses a variety of issues (biography, history, theory, methodology…) that throw light on the peculiarity of John L. Austin and his philosophy, as well as on the rejection generated against it. From all these aspects, this study intends to highlight the stylistic and discursive ones, especially the role of rhetoric, whit the aim to show that this author creates a performative prose in line with its intellectual content. In this way, Austin gives to his work a unique coherence between content and form.